(untitled) (CIPEEX, 2022)
Down Syndrome (DS) is a genetic condition characterized by a chromosomal abnormality1,2. There is a variability of deficits in the learning process and in the development of motor skills with a delay in the acquisition of basic motor milestones, impacting3,5 selective motor control, compromising motor acquisitions and the functional independence of the individual4. In the field of assessments, there is currently the use of human movement analysis of upper limbs (UL)6., the kinematics of upper limb movement in children has already been addressed in several studies6, 7 with excellent results, the association of brain activity assessment with the use of electroencephalogram can provide a comprehensive evaluation of motor adaptation through the simultaneous study of biomechanical and electroencephalographic evidence, being able to clarify how the motor and brain activity of individuals with neurological diagnoses differs from normal movement patterns during the preparation, execution, and post-execution phases of a task8. Given all the deficits mentioned in the field of rehabilitation, we have classical kinesiotherapy applied to the improvement of motor function in individuals with DS. we have classical kinesiotherapy with kinesiotherapy that generates beneficial9 effects, and currently, we have the use of gametherapy with the purpose of promoting movement repetition through functional and motor training10. Thus, the objective of the present study is to conduct a comparative analysis between the effects of ten sessions of upper limb gametherapy training and kinesiotherapy on the functionality, movement pattern (spatio-temporal parameters, kinematics), and brain and muscle activity of children with Down syndrome.